The Effectiveness of CSR Implementation in the Upstream Supply Chain of Mining Industry: A Stakeholders' Perspective - Nisya Medina Arinnis; Cahyaningratri Cahyaningratri; Priyotomo Priyotomo (Research Horizon, 2022)
The case study has derived from an Indonesian geothermal company established in 2008 that focused on one of its projects located in a mining site at Muara Laboh, Solok Selatan, Sumatra Barat, Indonesia. The purpose of this research is to identify the nature and form of Corporate Social Responsibility (CSR) initiatives conducted by the company at the Muara Laboh site; determine stakeholder contribution to the sustainability of CSR outcomes; analyse the relationship between stakeholders and the company; analyse the expectation differences between the company, stakeholder, and CSR/Stakeholder theory; identify future agenda development on the next stakeholder program; gives a reference for the subsequent research regarding a sustainable CSR program. The research method used in this research was a qualitative case study with a semi-structured interview as the source of primary data, where the population of this research was stakeholders of the company, with the method of purposive sampling for attaining the information. The study was imperative to learn the effectiveness of the company’s CSR in supporting stakeholders of the upstream supply chain. The result showed that the company has effectively implemented CSR for local communities in the Muara Laboh mining area. Moreover, local communities have had a good relationship and felt helped since the company came to their villages. However, there has been some expectation discrepancy between the company and local people. The distinction happened because the locals wanted material things such as donations and infrastructure. Nevertheless, they need more economic empowerment programs that can support sustainability or programs that can generate long-term benefits, not only material things that will run out if not used properly